Near‐Infrared‐II Nanomaterials for Fluorescence Imaging and Photodynamic Therapy. Issue 9 (18th February 2021) - Lin, Hongxin; Lin, Zexi; Zheng, Konghua; Wang, Chenlu; Lin, Lisheng; Chen, Jianxin; Song, Jibin
Abstract: Fluorescence (FL) imaging and photodynamic therapy (PDT) are popular in the diagnosis and treatment of diseases, respectively, especially in cancer. The excitation of the laser in the second near‐infrared (NIR‐II) window can effectively avoid the interference of spontaneous fluorescence and light scattering of tissues, obtaining high‐resolution images at deeper penetration depth. Due to their ideal spectral absorbance and high conversion efficiency, nanomaterials with emission at NIR‐II window not only overcome the absorption or emission of NIR‐II light by endogenous biomolecules, but also facilitate NIR‐II FL imaging and the application of photodynamic therapy (PDT). The research progress of NIR‐II nanomaterials for FL imaging and PDT in recent years is reviewed. First, the NIR‐II FL imaging of several representative organic and inorganic materials is introduced, including their remarkable properties and synthesis methods. Then, the use of NIR‐II nanomaterials in PDT, such as NIR‐II FL imaging‐guided PDT, and PDT combined with photothermal therapy is described. Finally, some critical challenges and open problems are proposed that need to be addressed in synthetic technology and clinical application. Abstract : This paper introduces NIR‐II fluorescence (FL) imaging of several representative organic and inorganic materials, including their remarkable properties and synthetic methods. Then, it demonstrates the application of NIR‐II nanomaterials in NIR‐II FL imaging‐guided photodynamic therapy (PDT), and PDT combined with photothermal therapy. Finally, it proposes some critical challenges that need to be addressed in synthetic technology and clinical application.